2018
DOI: 10.1101/301895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenomics reveals dynamic evolution of fungal nitric oxide reductases and their relationship to secondary metabolism

Abstract: Fungi expressing P450nor, an unconventional nitric oxide (NO) reducing cytochrome P450, are thought to be significant contributors to soil nitrous oxide (N2O) emissions. However, fungal contributions to N2O emissions remain uncertain due to inconsistencies in measurements of N2O formation by fungi. Much of the N2O emitted from antibiotic-amended soil microcosms is attributed to fungal activity, yet fungal isolates examined in pure culture are poor N2O producers. To assist in reconciling these conflicting obser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 113 publications
(158 reference statements)
1
6
0
Order By: Relevance
“…The ~10-fold increase in both N 2 O and CO 2 production by P. lilacinum grown with 100 mM NO − 2 (compared to 10 mM ) further supports the notion that respiratory reduction of NO − 2 was the primary mechanism for N 2 O production, although we cannot rule out the possibility that secondary metabolisms also contribute to N 2 O production (Higgins et al, 2018). Such a response by P. lilacinum implies that fungal N 2 O production from salt marsh sediments will scale linearly with nutrient inputs from anthropogenic sources.…”
Section: The Influence Of Cultivation Conditions On Fungal N 2 O Prod...supporting
confidence: 57%
See 4 more Smart Citations
“…The ~10-fold increase in both N 2 O and CO 2 production by P. lilacinum grown with 100 mM NO − 2 (compared to 10 mM ) further supports the notion that respiratory reduction of NO − 2 was the primary mechanism for N 2 O production, although we cannot rule out the possibility that secondary metabolisms also contribute to N 2 O production (Higgins et al, 2018). Such a response by P. lilacinum implies that fungal N 2 O production from salt marsh sediments will scale linearly with nutrient inputs from anthropogenic sources.…”
Section: The Influence Of Cultivation Conditions On Fungal N 2 O Prod...supporting
confidence: 57%
“…The ability to produce N 2 O was widespread among the hundreds of strains tested by Maeda and colleagues (Maeda et al, 2015), but only one (Mucorales) of the 70 N 2 O-producing strains in their study was not from the phylum Ascomycota. A survey of P450nor in over 700 fungal genomes also showed that this diagnostic gene for fungal denitrification was primarily found in Ascomycota (Higgins et al, 2018). While Ascomycota seem to be the main lineage capable of N 2 O production, fungi from other phyla, particularly early diverging lineages, are poorly represented in these studies, partially due to their low abundance in terrestrial environments (Berbee et al, 2017).…”
Section: N 2 O Production By Salt Marsh Sediment Fungimentioning
confidence: 94%
See 3 more Smart Citations